Neurological damages in COVID‐19 patients: Mechanisms and preventive interventions - Sibani Sarkar; Subhajit Karmakar; Malini Basu; Pratyasha Ghosh; Mrinal K Ghosh (MedComm)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), a novel coronavirus, causes coronavirus disease 2019 (COVID‐19) which led to neurological damage and increased mortality worldwide in its second and third waves. It is associated with systemic inflammation, myocardial infarction, neurological illness including ischemic strokes (e.g., cardiac and cerebral ischemia), and even death through multi‐organ failure. At the early stage, the virus infects the lung epithelial cells and is slowly transmitted to the other organs including the gastrointestinal tract, blood vessels, kidneys, heart, and brain. The neurological effect of the virus is mainly due to hypoxia‐driven reactive oxygen species (ROS) and generated cytokine storm. Internalization of SARS‐CoV‐2 triggers ROS production and modulation of the immunological cascade which ultimately initiates the hypercoagulable state and vascular thrombosis. Suppression of immunological machinery and inhibition of ROS play an important role in neurological disturbances. So, COVID‐19 associated damage to the central nervous system, patients need special care to prevent multi‐organ failure at later stages of disease progression. Here in this review, we are selectively discussing these issues and possible antioxidant‐based prevention therapies for COVID‐19‐associated neurological damage that leads to multi‐organ failure.